Analyzing of UV Index with the Time Variation for Baghdad - Ahmed Alwan; Ahmed Hameed; Nuha Hamad (Iraqi Journal of Industrial Research)
In order to better realize the effects of UV index (UVI) reaching the earth surface, measurements of effective UVI were carried out during the period of one year over Baghdad; (Lat.33.32- Long.44.45), which receives highly amounts of annual solar radiation. A daily data analysis of UVI is found to reach the highest value during summer reaching the value of 11, and a minimum in winter with the value of 1. A relation between UV index and the solar zenith angle was also, it is found that the UVI is highly dependent on the sun elevation where the atmospheric optical path becomes shorter as sun elevation heighten. It can be concluded that Baghdad city exposure to higher amounts of UVI during summer and several hedges must be taken to avoid health harm implications.